The Dose-Response Effects of Consuming High Fructose Corn Syrup-Sweetened Beverages on Hepatic Lipid Content and Insulin Sensitivity in Young Adults - Desiree M. Sigala (Nutrients, 2022)
Increased hepatic lipid content and decreased insulin sensitivity have critical roles in the development of cardiometabolic diseases. Therefore, our objective was to investigate the dose-response effects of consuming high fructose corn syrup (HFCS)-sweetened beverages for two weeks on hepatic lipid content and insulin sensitivity in young (18–40 years) adults (BMI 18–35 kg/m2). In a parallel, double-blinded study, participants consumed three beverages/day providing 0% (aspartame: n = 23), 10% (n = 18), 17.5% (n = 16), or 25% (n = 28) daily energy requirements from HFCS. Magnetic resonance imaging for hepatic lipid content and oral glucose tolerance tests (OGTT) were conducted during 3.5-day inpatient visits at baseline and again at the end of a 15-day intervention. During the 12 intervening outpatient days participants consumed their usual diets with their assigned beverages. Significant linear dose-response effects were observed for increases of hepatic lipid content (p = 0.015) and glucose and insulin AUCs during OGTT (both p = 0.0004), and for decreases in the Matsuda (p = 0.0087) and Predicted M (p = 0.0027) indices of insulin sensitivity. These dose-response effects strengthen the mechanistic evidence implicating consumption of HFCS-sweetened beverages as a contributor to the metabolic dysregulation that increases risk for nonalcoholic fatty liver disease and type 2 diabetes.